Johor dalam konteks ekonomi global - Khadijah Md. Khalid; Shakila Yacob; atimah Kari; Sharifah Mariam Alhabshi; Roslinda Ithnin; Sumiani Yusoff (University of Malaya Press, 2017)
On economic development in Johor, Malaysia